Complementary protective effects of autophagy and oxidative response against graphene oxide toxicity in Caenorhabditis elegans - Dou, Tingting; Chen, Jingya; Wang, Rui; Pu, Xiaoxiao; Wu, Huazhang; Zhao, Yunli (Ecotoxicology and environmental safety, 2022)
Graphene oxide (GO) exposure may cause damage to C. elegans. However, the role of autophagy and its interactive effect with oxidative response in GO toxicity still remain largely unclear. In the present study, we investigated the protective role of autophagy against GO and its association with oxidative response using C. elegans as an in vivo system. Results indicated that GO exposure induced autophagy in a dose dependent manner in C. elegans. Autophagy inhibitor 3-methyladenine (3-MA) and silencing autophagy genes lgg-1, bec-1 and unc-51 exacerbated the toxicity of GO whereas autophagy activator rapamycin alleviated it. In addition, the antioxidant N-Acetyl-L-cysteine (NAC) effectively suppressed the toxicity of GO with increased resistance to oxidative stress. Worms with RNAi-induced antioxidative genes sod-1, sod-2, sod-3 and sod-4 knockdown were more sensitive to GO. 3-MA increased the expression of superoxide dismutase SOD-3 under GO exposure conditions and exacerbated the toxicity of GO under the anti-oxidation inaction condition by sod-3 RNAi. In contrast, NAC reduced autophagy levels in GO exposed nematodes and increased tolerance to GO in autophagy-defective worms. These results suggested that autophagy and antioxidative response provide complementary protection against GO in C. elegans. [Display omitted] •Autophagy exerts a protective response to cope with the toxicity of GO in C. elegans.•Oxidative response plays a protective role in response to GO in C. elegans.•Autophagy and oxidative act in a complementation way in the protective response.